Analisis Pengaruh Standar Audit Syariah terhadap Kualitas Penyajian Laporan Keuangan Pada Baitul Mal wa Tamwil di Kabupaten Wonogiri - Rahmadieni, Risky Yuniar; Qizam, Ibnu (Universitas Muhammadiyah Malang, 2019)
The purpose of this study was to determine the extent to which the Statement of Islamic Accounting Standards, Sharia Audit, Sharia Supervision, Islamic Corporate Governance, and Islamic Work Ethos affect the Quality of Sharia Financial Statement Presentation in the Baitul Wat Mal of Wonogiri Regency Regional Office. This study uses a quantitative approach. Samples were taken by convenience sampling method. The research objects encompass five BMT?s located approximately 10 km away from the Wonogiri Regent's Office which consists of three sub-districts, namely Selogiri, Wonogiri, and Ngadirojo. 35 questioners are processed and analyzed using SPSS Version 23. Based on the results of this study, there are many effects of statement of Islamic accounting standards and Islamic work ethos on the quality presentation of Islamic financial statements.